Digital Era: What Can Parents Do to Prevent Uncontrolled Screen Time in Young Children? - Azizah Nurul,Fadlilah (Annual Conference on Islamic Early Childhood Education (ACIECE), 2022)
As a result of Covid-19, children's screen time has increased. This habit still occurs today after the pandemic. In fact, excessive screen time can have various negative impacts on children. This study aims to analyze the application of screen time and ways that can be done to prevent uncontrolled screen time in early childhood. This type of qualitative research uses data collection techniques using questionnaires and interviews. The data sources in this study consisted of 53 respondents from 24 different cities in Indonesia. Data were analyzed using data analysis techniques by Miles and Huberman. The study results show that several efforts can be made to prevent uncontrolled screen time in young children, namely with disciplined regulations, parental supervision, positive diversion activities, and setting screen time on digital media. Some of these methods can be used by parents to prevent uncontrolled screen time in their children.